Research and design of interface for audio and video secure communication system - A.V. Cherepanov; A.A. Mavrichev; A.G. Dolmatov; A.S. Luchinin; I.V. Malygin (Физика волновых процессов и радиотехнические системы, 2017)
Currently, audio-video information can be transmitted by various communication systems such as WiFi, WiMAX, LTE, or 3G. Despite the fact that these systems fulfill their functions quite well, they are united by a common drawback - they are not designed to work in conditions of strong interference. To transfer audio-video information in the presence of strong interference, the authors have developed a data transfer system using spread spectrum signals. This article is devoted to the design, configuration and interface study of how to link this system with standard sources and receivers, both audio and video.